2022
DOI: 10.1002/pbc.29546
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health and pediatric cancer survival: A systematic review

Abstract: Despite treatment advancements and improved survival, approximately 1800 children in the United States will die of cancer annually. Survival may depend on nonclinical factors, such as economic stability, neighborhood and built environment, health and health care, social and community context, and education, otherwise known as social determinants of health (SDoH). Extant literature reviews have linked socioeconomic status (SES) and race to disparate outcomes; however, these are not inclusive of all SDoH.Thus, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…In particular, the impact of household material hardship and adverse social determinants of health (SDOH) on pediatric oncology patients is well established in the literature. [38][39][40] Although the gains achieved in cure rates in pediatric oncology may be attributed in large part to clinical trial organizations, children living in poverty and those identified as being from marginalized racial, ethnic, and minority groups are more likely to relapse and die at rates different from their non-Hispanic White counterparts. [41][42][43][44] Biology, tumor genetics, and response to initial therapy aside, pre-existing social and psychological factors, including SDOH, play a significant role in patient outcomes.…”
Section: Prioritizing Social Determinants Of Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the impact of household material hardship and adverse social determinants of health (SDOH) on pediatric oncology patients is well established in the literature. [38][39][40] Although the gains achieved in cure rates in pediatric oncology may be attributed in large part to clinical trial organizations, children living in poverty and those identified as being from marginalized racial, ethnic, and minority groups are more likely to relapse and die at rates different from their non-Hispanic White counterparts. [41][42][43][44] Biology, tumor genetics, and response to initial therapy aside, pre-existing social and psychological factors, including SDOH, play a significant role in patient outcomes.…”
Section: Prioritizing Social Determinants Of Healthmentioning
confidence: 99%
“…The BSC strongly supports ongoing work to identify and address health disparities in pediatric and AYA cancer care. In particular, the impact of household material hardship and adverse social determinants of health (SDOH) on pediatric oncology patients is well established in the literature 38–40 …”
Section: Strategic Plan: Opportunities and Future Directionsmentioning
confidence: 99%
“…Racial disparities have been found across the entire trajectory of childhood cancer from the point of access into the healthcare system to mortality risk and quality of life in long-term survivors. 8,9,26 Structural racism in the form of economic, social, and cultural forces likely contributes to a complex causality for these racial disparities. Structural racism perpetuates the association between race and socioeconomic and power gradients in society via legislation, policy, and societal norms that systematize neighborhood segregation.…”
Section: Implications For Future Research and Clinical Practicementioning
confidence: 99%
“…[3][4][5][6][7] Based on their systematic review of the extant literature, Beltrami et al 8 concluded that social and cultural forces likely contribute to a complex causality for these racial disparities beyond biological differences alone. In a second review of the current literature published between 2009 and 2021, Tran et al 9 identified gaps in our understanding of the mechanisms underlying these persistent disparities, citing the absence of social and cultural factors at both the individual and community levels in the research of childhood cancer survivorship.…”
mentioning
confidence: 99%
“… 12 , 13 , 14 , 15 In a systematic review by Tran et al., in 2022, inconsistent findings have been found on the association of SDoH and paediatric cancer. 16 In a prospective study on the topic, Bona et al. found that 20% of the 99 families with children receiving chemotherapy for a primary cancer had income ≤200% the federal poverty line and at least one episode of a food, energy, or housing insecurity.…”
Section: Introductionmentioning
confidence: 99%